Ruang dan Kultur Pengalaman Gigolo Eksklusif di Surabaya - Sarmini Sarmini; Anna Lutfaidah; Ajeng Eka Prastuti (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
The existence of students in the community should play a role as a drafter, dynamist, and evaluator of various social changes. Something that has a positive impact on the community. But some of them do the opposite, having a negative impact on the community, such as acting as a gigolo, known as ‘exclusive gigolo’. This research presents the meaningful actions carried out by exclusive gigolo to attract sympathy and various actions in providing excellent service to clients. These actions were examined from the perspective of Max Weber's Theory of Social Action. This research used a qualitative approach with the perspective of Weber's theory. The research subjects were students who worked as gigolos, ranging from freelance to a lover (manstress). The informants were selected using the snowball sampling technique. Meanwhile, the data collection technique used is in-depth interviews. Data analysis and interpretation techniques are carried out with a deeper understanding (verstehen). There are gigolo social actions, within the framework of norm values, which become the blueprint of community behavior. First, the integration between rationality actions and instrumental rationality actions. These actions were found in activities, including: (1) Gigolo built his self-image: from self-expertise to intelligence in choosing marketing models; (2) Ignoring the feeling of shame as self-strengthening in facing various situations; (3) Client service actions: from holding hands to sexual activity. Second, the integration between rationality action and affective action. The highest achievement for gigolo is to become a lover (manstress). The intensity and the close relationship between a gigolo and the client can make both of them fall in love, like real love. In this context, the gigolo puts money as its main goal. On the other hand, gigolo realizes that the woman who is his client has a family, so it is impossible to have the love of the woman completely. This research concluded that: (1) The implementation of Max Weber's Theory of Social Action in gigolo social actions is integrated into one action with another, and; (2) Gigolo does not take traditional actions on the actions that have been taken.